Efektivitas Pembatasan Sosial Berskala Besar di Indonesia Dalam Penanggulangan Pandemi Covid-19 - Sylvia Hasanah Thorik (UIN Syarif Hidayatullah Jakarta, 2020)
Abstract:Large-scale social restrictions in Indonesia are strategic steps taken by the government to reduce the rate of transmission of the Corona Virus pandemic or Covid-19. How effective the step is, all parties still see in advance the impact going forward. However, we all hope that the steps taken by the government in implementing this PSBB are the best steps and can run as they should, and economic growth and financial stability can be maintained, so that some economic activity in Indonesia can still be carried out, even with social constraints more stringent and massive.Keywords: PSBB, COVID-19 Abstrak:Pembatasan Sosial Berskala Besar di Indonesia merupakan langkah strategis yang diambil oleh pemerintah guna menekan laju penularan pandemi Corona Virus atau Covid-19. Seberapa efektif langkah tersebut, semua pihak masih melihat terlebih dahulu dampak ke depannya. Namun, kita semua berharap bahwa langkah yang diambil pemerintah dalam menerapkan PSBB ini adalah langkah yang terbaik dan dapat berjalan sebagaimana mestinya, serta pertumbuhan ekonomi dan stabilitas keuangan tetap dapat terjaga, sehingga beberapa aktivitas perekonomian di Indonesia masih dapat dijalankan, walaupun dengan batasan-batasan sosial yang lebih ketat dan massif.Kata Kunci: PSBB, COVID-19